Towards more power-sensitive teacher’s written feedback: a critical review of authority - Nancy Mohamed Afifi; Shaker Rizk; Inas Hussein Hassan; Riham Debian (Insights into Language, Culture and Communication, 2025)
This review critically examines the role of teacher-written feedback in negotiating authority within higher education, focusing on its linguistic, rhetorical, and institutional dimensions. Drawing on Critical Discourse Analysis (CDA), Speech Act Theory, and Moves Analysis, it explores how feedback acts not only as instruction but also as a mechanism of power, shaping student agency, identity, and engagement. The article categorizes feedback into control-based, scaffolding-based, and empowerment-oriented types, analyzing how linguistic features imperatives, modal verbs, evaluative adjectives, and rhetorical questions shape perceptions of authority. Empirical studies and existing models, including the Feedback Literacy Behaviour Scale (FLBS), Socio-Constructivist Feedback Model, and Value-Added Modeling (VAM), are reviewed for their capacity to assess power dynamics in written feedback. Findings show that overly directive feedback can suppress autonomy, while dialogic, student-centered practices foster engagement and critical thinking. A mixed-methods framework is proposed to evaluate feedback authority, combining linguistic analysis with student perceptions and revision outcomes. The review concludes by highlighting pedagogical and theoretical implications, advocating culturally responsive practices and integration of power-sensitive strategies in teacher training and institutional policy, with future research aimed at empirical validation and cross-cultural adaptation.   Received on: 03 April 2025 Accepted on: 06 May 2025 Published on: 27 May 2025